Roald Dahl charlie and the great glass elevator - Dahl,Roald (London: Penguin Group, 1973)
Charlie and the Great Glass Elevator is a 1972 children's novel by Roald Dahl and is a sequel to Charlie and the Chocolate Factory. The story picks up immediately after the first book, with Charlie Bucket and his family taking a ride in Willy Wonka's magical glass elevator. However, things quickly spiral out of control when the elevator shoots up into space, and the group finds themselves aboard a space hotel. In the elevator, they encounter a number of adventures, including a dangerous encounter with a group of hostile space creatures called the "Whangdoodles." Meanwhile, a crisis is unfolding on Earth as the elevator accidentally causes a threat to the President of the United States and the White House. Throughout their adventures, Charlie and his family demonstrate kindness and bravery, while Willy Wonka's eccentricity and genius continue to guide them through their challenges. The story is full of whimsy, imagination, and Dahl$1 (Bs signature sense of humor, with a final resolution that sees the family safely back on Earth, continuing their journey with Willy Wonka in his ever-wondrous world.s
Sequel to Charlie and the Chocolate Factory: The book follows Charlie Bucket and his family shortly after they win a golden ticket to Willy Wonka's chocolate factory, as they embark on a new adventure in the magical glass elevator. Plot Overview: The story begins with Charlie and his family traveling in the Great Glass Elevator, a flying contraption designed by Willy Wonka. They accidentally shoot into space, where they encounter a space hotel, strange creatures, and a series of chaotic events. They also unintentionally create a dangerous situation on Earth, where the President of the United States and the White House are put at risk. Main Characters: Charlie Bucket: The kind-hearted, humble boy who remains the protagonist of the story, filled with wonder and curiosity. Willy Wonka: The eccentric and genius chocolatier, who is constantly in control of the fantastic situations but sometimes makes mistakes due to his over-the-top inventions. The Bucket Family: Charlie$1 (Bs parents and grandparents, who join him on his adventure. The President: An important but often comical character who appears during a key plot point when the glass elevator flies near the White House. Themes: Adventure and Exploration: The book emphasizes adventure, with its journey into space and the thrilling events that follow. Invention and Imagination: The fantastical inventions of Willy Wonka play a major role, particularly the glass elevator and the other whimsical elements of the story. Kindness and Courage: Charlie$1 (Bs good nature continues to shine through, as he faces challenges with bravery and compassion. Humor: The story is filled with Dahl$1 (Bs signature quirky humor, including absurd situations and witty dialogue. Space Setting: A large portion of the book takes place in space, where the characters visit a space hotel and face bizarre space creatures, such as the "Whangdoodles" and the "Vermicious Knids." Tone and Style: Roald Dahl's storytelling is playful and imaginative, with an adventurous and sometimes mischievous tone. The language is fun and exaggerated, and the humor often involves wordplay, absurdity, and the characters$1 (Bextreme personalities. Illustrations: The original book was illustrated by Joseph Schindelman, with lively and quirky illustrations that complement the fantastical world of Willy Wonka. Audience: The book is aimed at children, but like many of Dahl's works, it also appeals to adults with its humor and deeper moral lessons about human nature. Ending: The book concludes with Charlie and his family safely returning to Earth, leaving a sense of satisfaction and the idea that their journey with Willy Wonka will continue in future adventures.s
Keywords: Charlie Bucket; Space Adventure